The Science of Sustaining Health Behavior Change: The Health Maintenance Consortium - Ory, Marcia G. (2010)
OBJECTIVE: The Health Maintenance Consortium (HMC) is a multisite Grantee Consortium funded by the National Institutes of Health from 2004–2009. The goal of HMC is to enhance understanding of the long-term maintenance of behavior change, as well as effective strategies for achieving sustainable health promotion and disease prevention. METHODS: This introductory research synthesis prepared by the Resource Center gives context to this theme issue by providing an overview of the HMC and the articles in this journal. RESULTS: It explores the contributions to our conceptualization of behavior change processes and intervention strategies, the trajectory of effectiveness of behavioral and social interventions, and factors influencing the long-term maintenance of behavioral and social interventions. CONCLUSIONS: Future directions for furthering the science of maintaining behavior change and reducing the gaps between research and practice are recommended.